The welfare effects of changes in global food prices on income distribution in Turkey - Akar, Hüseyin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study examines the pass-through effects of global food prices on food prices in Turkey, and the welfare effects of food price changes on income distribution in Turkey. Food products are the indispensable part of the consumption basket for entire households, especially for low-income groups. Therefore, food price changes can directly inﬂuence the living conditions of people positively or adversely. To ﬁgure out these impacts in Turkey, we ﬁrst obtain the pass-through coefﬁcients for the selected food groups using econometric tools. Then, we integrate these coefﬁcients and Turkish household groups, which are divided into ﬁve brackets based upon nominal income, into the CGE analysis. This analysis allows us to estimate how an economy can react to changes in a part of the economy under the determined framework. Finally, we apply both a positive 5% shock and a negative 5% shock to world food prices. According to the ﬁndings, the income of all household groups declines when global food prices surge. However, rising food prices have a more adverse effect on low-income household groups, and accordingly distort income distribution in Turkey. Inversely, under the scenario wherein world food prices decline, low-income households are affected more positively in wealth terms. It is observed that income distribution in Turkey recovers slightly. Meanwhile, disruptive impact of increased food prices is stronger than remedial impact of tumbled prices on income distribution.
Keywords: Food prices.; Food prices -- Government policy -- Turkey.; Agriculture -- Economic aspects.; Income -- Turkey.